The Synthesis, Characterization, and Anticancer Activity of New 2-acetylbenzofuran-Chalcone Hybrids - Coskun, Demet; Dalkilic, Semih; Dalkilic, Lutfiye Kadioglu; Coskun, Mehmet Fatih (Springer Int Publ Ag, 2021)
This study deals with the design of original benzofuran-chalcone hybrids as anticancer agents. First, the reaction of 6-methoxysaliciylaldehyde with chloroacetone and potassium carbonate was used to prepare 1-(6-methoxy-1-benzofuran2-yl) ethanone (1) as a starting reagent. A novel series of chalcone derivatives 3a-h, obtained through Claisen-Schmidt condensation with aromatic aldehydes 2a-h containing 6-methoxy benzofuran moiety, was designed, synthesized, and evaluated in terms of anticancer activities. The synthesized compounds 3a-h were tested against two MDA-MB-231 (human breast cancer cell line) and A549 (human lung cancer cell line) in order to detect anticancer activity by MTT Assay. The results revealed that 2-acetylbenzofuran-chalcone hybrids have an anticancer effect, especially with the phenolate salt of chalcone derivative 3e which shows cytotoxic effects on lung cancer cells. These observations showed that novel hybrid chalcone derivatives with a phenolate and methoxy linked 2-acetylbenzofuran prodrug strategy would be an important and easy method to increase water solubility and anticancer activity.
Keywords: Benzofuran; Chalcone; Hybrid compounds; Cytotoxic activity; Anticancer activity